The Evolving Theory of Evolutionary Radiations. (January 2016) - Simões, M.; Breitkreuz, L.; Alvarado, M.; Baca, S.; Cooper, J.C.; Heins, L.; Herzog, K.; Lieberman, B.S.
Abstract : Evolutionary radiations have intrigued biologists for more than 100 years, and our understanding of the patterns and processes associated with these radiations continues to grow and evolve. Recently it has been recognized that there are many different types of evolutionary radiation beyond the well-studied adaptive radiations. We focus here on multifarious types of evolutionary radiations, paying special attention to the abiotic factors that might trigger diversification in clades. We integrate concepts such as exaptation, species selection, coevolution, and the turnover-pulse hypothesis (TPH) into the theoretical framework of evolutionary radiations. We also discuss other phenomena that are related to, but distinct from, evolutionary radiations that have relevance for evolutionary biology. Trends: Evolutionary radiations involving diverse clades are of significant relevance to evolutionary biologists; as a subset they include adaptive radiations. Several processes beyond adaptive radiation can produce highly diverse clades; a broad perspective is necessary to gain insight into the pantheon of evolutionary radiations. A clade might be diverse because it has experienced extensive opportunities for geographic isolation and allopatric speciation. Key concepts from macroevolutionary theory such as species selection and the TPH are relevant. Diverse clades can arise from increasing speciation rate or declining extinction rate; different processes would be involved. Episodes of rapid speciation can be decoupled from episodes of pronounced morphological change, and signify different processes.